Autonomy and Power : the Dynamics of Class and Culture in Rural Bolivia - Lagos, Maria L. (The Ethnohistory Series, 2016)
Maria L. Lagos supplies a fine-grained ethnographic and historical analysis of the intersecting dynamics of class and culture in Tiraque, a province in the highlands of Cochabamba, Bolivia.